Income, Saving, and the Theory of Consumer Behavior (Book). - Cannon, Arthur M.; Ellis, Paul W. (The Accounting Review, 1950)
Abstract Reviews the book "Income, Saving, and the Theory of Consumer Behavior," by James S. Duesenberry.